triangles

Asked by  | 12th Feb, 2009, 10:04: PM

Expert Answer:

Draw AE BC

AS ABC is isosceles traingle, BE = EC

In triangle ABD

AB2=AE2+BE2

In triangle ADE

AD2=AE2+ED2

Subtracting the two equations, we get

AB2-AD2=BE2-ED2

               = (BE+ED)(BE-ED)

              = BD.(BE-ED)

              = BD. (CE-ED)   (As BE=CE)

             = BD. CD

Hence, proved

Answered by  | 5th Mar, 2009, 12:26: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.